Conservation laws, soliton-like and stability analysis for the time fractional dispersive long-wave equation - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Springer, 2018)
In this manuscript we investigate the time fractional dispersive long wave equation (DLWE) and its corresponding integer order DLWE. The symmetry properties and reductions are derived. We construct the conservation laws (Cls) with Riemann-Liouville (RL) for the time fractional DLWE via a new conservation theorem. The conformable derivative is employed to establish soliton-like solutions for the governing equation by using the generalized projective method (GPM). Moreover, the Cls via the multiplier technique and the stability analysis via the concept of linear stability analysis for the integer order DLWE are established. Some graphical features are presented to explain the physical mechanism of the solutions.
Keywords: Time fractional PDEs; RL fractional derivative; Cls; Solitons; Stability analysis